PENGGUNAAN MEDIA AJAR PADA PEMBELAJARAN SENI TARI DI TK KEMALA BHAYANGKARI ACEH SINGKIL - Taat Kurnita Yeniningsih; Aida Fitri; Hayati (Jurnal Buah Hati, 2019)
Media is a communication channel that determines the success of learning. Basically learning media is useful to make it easier for students to understand something that is possible difficult or simplifying something that might be complex. This study aims to describe the use of teaching media in dance learning and what obstacles are found by teachers in the learning process of dance by using teaching media at TK Kemala Bhayangkari. The approach of this research is qualitative with descriptive type. Data collection techniques by observation, interviews, documentation. Data Analysis with data reduction, data presentation, data verification. This research was conducted at TK Kemala Bhayangkari Aceh Singkil. Based on the research data, the use of teaching media in dance learning and the obstacles found by the teacher in the process of learning dance using teaching media in kindergarten Kemala Bhayangkari can be summarized as follows: The use of audio-based media is very effective in motivating and improving student learning outcomes. The group of students in learning the bungong seulanga dance. The obstacle that was found was the disruption of the concentration of students caused by interference from the side of his friends who were impatient to play, so that the teacher had to be more serious in paying attention to the students in following the learning. Abstrak Media merupakan saluran komunikasi penentu keberhasilan pembelajaran. Pada dasarnya media belajar berguna untuk memudahkan peserta didik memahami sesuatu yang mungkin sulit atau menyederhanakan sesuatu yang mungkin kompleks. Penelitian ini bertujuan untuk mendeskripsikan penggunaan media ajar pada pembelajaran seni tari dan hambatan-hambatan apa saja yang di temukan guru pada proses pembelajaran seni tari dengan menggunakan media ajar di TK Kemala Bhayangkari. Pendekatan penelitian ini adalah kualitatif dengan jenis deskriptif. Teknik pengumpulan data dengan observasi, wawancara, dokumentasi. Analisis Data dengan reduksi data, penyajian data, verifikasi data. Penelitian ini dilakukan di TK Kemala Bhayangkari Aceh Singkil. Berdasarkan data hasil penelitian penggunaan media ajar pada pembelajaran seni tari dan hambatan-hambatan yang di temukan guru pada proses pembelajaran seni tari dengan menggunakan media ajar di TK Kemala Bhayangkari dapat di simpulkan sebagai berikut: Penggunaan media berbasis audio sangat efektif dalam memotivasi dan meningkatkan hasil belajar peserta didik. Kelompok peserta didik dalam pembelajaran seni tari bungong seulanga. Hambatan yang di temukan adalah terganggunya konsentrasi peserta didik yang diakibatkan oleh gangguan dari pihak temannya yang tidak sabar untuk bermain, sehingga guru harus lebih serius memperhatikan peserta didik dalam mengikuti pembelajaran. Kata kunci: Media ajar, taman kanak-kanan